(3EUdGM GdNdd GdhGbY aj cJGH GdLeds - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s; (3YHO GdQMef Hf ESMGb GdfgGhfOj GdRLGLj, CHh GdbGSe,J (B377 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd GdHWdjhSi EjVGM eYGfi CHjGJ cJGH GdLed hEUdGM eG hbY ajg ef GdNdd GdcJGH GdChd HSe Gddg GdQMef GdQMje eSFdg bGd CHh GdbGSe GdRLGLi GdfMhi s
(3BNQgG (B:s
(3HGH GdJUQja bGd CHh GdbGSe ai gPG GdHGH GdKGfi efg hef GdYQH ef jLQi GdeYJd ef gPG GdLfS hbO LYd CHh GdbGSe EdMGb GdeYJd HGdUMjM ef VQhQI GdTYQ ajeG JbOe hLYdg gGgfG dZI ceG JQi hGddg CYde Je cJGH EUdGM GdNdd GdhGbY ai cJGH GdLed s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hQO ai cTa GdXfhf L (B1 (3U` (B603 (3Cf cJGH GdLed dCHh GdbGSe GdRLGLi GdfMhi s
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs